Evaluating the Therapeutic Potential of Cenicriviroc in the Treatment of Nonalcoholic Steatohepatitis with Fibrosis: A Brief Report on Emerging Data - Diaz Soto MP (Dove Medical Press, 2020)
Maria Paula Diaz Soto,1 Joseph K Lim2 1Department of Medicine, Yale School of Medicine, New Haven, CT, USA; 2Yale Liver Center and Section of Digestive Diseases, Yale School of Medicine, New Haven, CT, USACorrespondence: Joseph K LimProfessor of Medicine, Yale Liver Center and Section of Digestive Diseases, Yale School of Medicine, 333 Cedar Street, LMP 1080, New Haven, CT 06520-8019, USATel +1 (203) 737-6063Fax +1 (203) 785-7273Email joseph.lim@yale.eduAbstract: Non-alcoholic steatohepatitis (NASH) is associated with significant morbidity and mortality due to liver cirrhosis, liver failure, and hepatocellular carcinoma, and represents a leading indication for liver transplantation in the United States (U.S.). A growing spectrum of novel therapies are currently in clinical development and target several mechanisms of action which address hepatic steatosis, steatohepatitis, and hepatic fibrosis. Cenicriviroc (Allergan, Dublin, Ireland) is a novel oral antagonist of CC-motif chemokine receptors 2 and 5 (CCR2/5) which have demonstrated expression on circulating monocytes and Kupffer cells. Preclinical models have confirmed that CCR2/5 antagonism may block fat accumulation and Kupffer cell activation and disrupt monocyte/macrophage recruitment and hepatic stellate cell activation responsible for fibrogenesis. Herein we review results from the phase 2b CENTAUR trial and study designs for the phase 2b TANDEM and phase 3 AURORA trials and discuss the potential role of cenicriviroc in future pharmacotherapy for NASH fibrosis.Keywords: cenicriviroc, fatty liver, non-alcoholic steatohepatitis, liver fibrosis, antifibrotic therapy, clinical trials